Representaciones del tema del erotismo en pubis equinoccial de Raúl Vallejo - Paguay Gavidia, Diana Carolina (2025)
Since the beginning of time, sexuality has been a taboo for women, condemning their thoughts and actions. It has led to the repression and criticism of many women for so-called "indecent" behavior. For this reason, this research analyzes writing and narratives related to women's eroticism and sexuality. This study aimed to analyze eroticism in the contemporary short story Pubis Equinoccial by Raúl Vallejo. A qualitative methodology was employed, which helped to interpret essential parts of the book that supported the research objective. Additionally, hermeneutics was used as an analytical tool, facilitating the interpretation of phrases and symbols within the short stories. Finally, the study concluded that Pubis Equinoccial by Raúl Vallejo is a work that intertwines eroticism with a writing style rich in symbolism and emotional exploration. In these short stories, eroticism is not limited to the physical realm but becomes a means of intimate and existential connection between the characters. It highlights the importance of reading stories that do not restrict women's emotions and thoughts.